Unveiling Caribbean diversity: 11 new species of Venezillo Verhoeff, 1928 (Isopoda: Armadillidae) from Colombia and redescription of the type species - López-Orozco, Carlos Mario; Carpio-Díaz, Yesenia M.; Arrieta, Ricardo Borja-; Bravo-Rodríguez, Agustín E.; Gutierrez-Estrada, Miguel; Moreno, Jhon Cesar Neita; Taiti, Stefano; Bermúdez, Adriana; S., Gabriel R. Navas-; Campos-Filho, Ivanklin Soares (Zootaxa, 2026)
The genus Venezillo Verhoeff, 1928 is among the most diverse and widely distributed genera of terrestrial isopods in the Neotropical region, yet it remains poorly studied in much of South America. In this study, we revise the genus in the Colombian Caribbean and describe eleven new species, all collected from remnants of Tropical Dry Forest (TDF), one of the most threatened ecosystems in the region. We also provide redescriptions of V. clausus (Budde-Lund, 1885), the type species of the genus, based on material from Venezuela, and of V. grenadensis (Miers, 1877) and V. gigas (Budde-Lund, 1893), based on specimens from Grenada and Nicaragua, respectively. Our results reveal new diagnostic characters for the genus and highlight the importance of detailed male morphology for species delimitation. Ecological observations show that Venezillo species inhabit leaf litter and decaying wood in dry forest environments, with activity patterns potentially influenced by seasonal microclimatic variation. Finally, we present an updated checklist of Armadillidae in Colombia and emphasize major knowledge gaps and priorities for future research.